Java how to program late objects version - Deitel, Paul; Deitel, Harvey (Pearson Education Limited, 2015)
The Deitels' groundbreaking How to Program series offers unparalleled breadth and depth of object-oriented programming concepts and intermediate-level topics for further study. Java How to Program (Late Objects), Tenth Edition, teaches programming by presenting the concepts in the context of full working programs.